Ford sewing machinists, 1968 (1968)
1968 1960-2000 "Ford sewing machinists, 1968" [T0400.jpg], 1968 Women sewing machinists at the Ford Motor Company plant in Dagenham took strike action on 7 June, 1968 in support of a claim for regrading, parity with men in the C grade and recognition of their skills. After 3 weeks on strike they settled for 92% of the C grade rate. Although not an equal pay strike, the strike was given a high profile when the whole plant was closed and Barbara Castle, the Employment Minister, was brought in to help negotiate a settlement.